Tradicare: Sales Management and Appointment Booking System for Traditional Treatment - Sayuthi, Anwar; RAMLI, AZIZUL AZHAR (Applied Information Technology And Computer Science, 2025)
In the digital era, small businesses like Tradicare, a traditional treatment center in Pekan Parit Sikom, Johor, struggle with manual operations for appointments and sales, limiting growth. This project develops a web-based Sales Management and Appointment Booking System using Agile methodology and technologies like HTML, CSS, JavaScript, PHP, and MySQL. Key features include registration, product catalog, appointment scheduling, secure payments, and reporting. The system ensures efficiency through database normalization, real-time data handling, and encryption for security. Customers benefit from easy browsing, booking, and payments, while Tradicare gains automation, reduced errors, and analytics for decision-making. Modernizing operations helps expand market reach, improve customer satisfaction, and stay competitive. Future enhancements may include AI-driven health recommendations for personalized care.